Ocorrência de raiva em bovinos e equídeos no Estado de Rondônia: um estudo retrospectivo de 2002 a 2021 - (:unkn) unknown (Universidade Brasil, 2022)
Considering the importance of rabies encephalomyelitis in the herd of domestic herbivores in Brazil, the present work aims to present the results of the occurrence of rabies in cattle and equine herds in the state of Rondônia, between the years 2002 to 2021, as well as the actions carried out by IDARON (Agrosilvopastoril Defense Agency of the State of Rondônia) for the sanitary control of these disease. This is an epidemiological study based on official data provided by IDARON. From 2002 to 2021, 1713 laboratory tests were performed for the diagnosis of rabies, covering bovine, buffalo, equid, goat, sheep, swine, bat and capybara species. Of these, 83% of the samples were from cattle, resulting in 201 positive diagnoses of rabies, which represents 14% of cattle. As a sample of equines, they add up to 5% of the total number of exams carried out in this period. Twenty-three cases of rabies in equids were identified, representing 26% of equine exams. As a sample of bats, it corresponds to 8% of the total number of exams. Of these 3 were positive for rabies, which is equivalent to 2% of the examinations in bats. There was a reduction in the occurrence over the period, being statistically significant for the decrease in the incidence rate of positives per 10,000 properties. There was no seasonality in the occurrences in the different months of the year. However, there was a significant correlation between the findings of the incidence rate of positives when: shelter monitoring (77% negative correlation); number of captures (negative correlation of 52%); captured bats (negative correlation 51%); treatment of bats with anticoagulant paste (negative correlation of 54%); commercialization of vaccines against rabies (44%). All these findings together clearly demonstrate the importance and effectiveness of the actions established by IDARON in the control of rabies in the state of Rondônia, from 2002 to 2021.
Keywords: Raiva herbívora; Morcego; Desmodus rotundus; IDARON; Produção Animal